Dye-sensitized solar cells based on dimethylamino-π-bridge-pyranoanthocyanin dyes - Pinto, Ana Lucia (2022)
UID/QUI/50006/2019 PTDC/QEQ-QFI/1971/2014 PD/BD/135087/2017 SFRH/BD/136556/2018 SFRH/BD/143309/2019 IF/00225/2015 DL57/2016 Program Contract (HC). UID/CTM/50025/2019 PTDC/CTM-ENE/5125/2014 CNPq 444061/2018-5 Universal grant 408181/2016-3